Preparing Preservice Teachers for Critical Literacy Classrooms in Korea - Choi, Soo Joung (Secondary English Education, 2025)
Focusing on the experience of eight preservice teachers in Korea enrolled in a teacher education class that introduced critical literacy, this qualitative case study explores how they perceive critical literacy as a potential educational paradigm for teaching EFL (English as a foreign language) literacy and the way the class is closely related to their renewed understanding of literacy as well as their re-established pedagogical philosophies. The data were collected from reflection papers, interviews, the researcher’s reflective journals, and the preservice teachers’ critical literacy lesson plan, and were analyzed qualitatively. The findings illustrate that the preservice teachers embraced critical literacy with enthusiasm, thinking highly that it encourages learners to become active agents in producing meaning and enables them to tackle diverse social issues with a critical lens. Through their engagements with theory and practice in the class, they not only came to develop a language of critique but also moved beyond understanding literacy as basic reading and writing skills to viewing literacy as a learner’s ability to analyze texts critically. In addition, the preservice teachers began to consider learners valid knowledge co-constructors while breaking away from the banking model of education. KCI Citation Count: 0